The role of the social media platform pinterest as a creative media reference for generation Z students - Saputra, Relly Anjar Vinata Wisnu (English Learning Innovation, 2024)
This study was conducted to analyze the role of the social media platform Pinterest as a reference for the creativity of Generation Z students. The research method used was qualitative with a case study approach, allowing for an in-depth exploration of how Pinterest influences student creativity. Data collection techniques were carried out through in-depth interviews, observations, and document studies, ensuring a comprehensive understanding of the subject matter. Informants were determined purposively, consisting of students from the Department of Sociology at Universitas Negeri Padang, specifically from both the Sociology Study Program and the Communication Studies Program. This targeted selection ensured that the informants had relevant experience and insights. Data processing utilized the Miles and Huberman data analysis technique, which involves data reduction, data display, and conclusion drawing/verification. This method ensured that the data was systematically analyzed to identify patterns and draw meaningful conclusions. The results of the study indicate that Pinterest plays a crucial role in facilitating the creative processes of Generation Z students. This platform serves as a rich source of visual inspiration, offering a vast array of images and creative ideas that can stimulate the imagination of Generation Z students. Additionally, the ability to save and share creative content broadens the horizons of Generation Z students, enabling them to continuously develop their creative skills and expertise. Pinterest not only provides inspiration but also serves as a collaborative tool where students can exchange ideas and gain feedback from peers, further enhancing their creative potential